Taxonomic review of the pollen wasps (Hymenoptera: Vespidae: Masarinae) from the Caucasus, with the description of two new species, new nest and flower-visiting records, and a key to the species - Fateryga, Alexander V.; Mauss, Volker; Proshchalykin, Maxim Yu.; Maharramov, Mahir M. (Zootaxa, 2025)
Twelve species of the subfamily Masarinae from the Caucasus are reviewed. Two new species are described, namely Celonites carpenteri Fateryga & Mauss, sp. nov. (Nakhchivan Autonomous Republic of Azerbaijan) and Quartinia aliyevi Fateryga, Mauss, Proshchalykin & Maharramov, sp. nov. (Nakhchivan Autonomous Republic of Azerbaijan, Armenia). The hitherto unknown male of Celonites tudesculptus Kostylev, 1935 is described. Celonites osseus Morawitz, 1888, C. tudesculptus, and Quartinia araxana Giordani Soika, 1960 are reported for the first time from Azerbaijan. New flower-visiting records are documented for Celonites carpenteri, C. laetus Panfilov, 1968, C. tauricus Kostylev, 1935, C. tudesculptus, and Jugurtia eurycara Kostylev, 1935. Nests of Celonites ivanovi Mauss & Fateryga, 2022 are described for the first time. An identification key and maps detailing the geographic distribution of all species in the Caucasus are presented.